Story summarization using a story world graph - Adolfo, Bianca Trish (Animo Repository, 2017)
Story summarization is a relatively unexplored field. This research aims to create a story summarization system using a story world graph for knowledge representation. The summarization system would take a story as input and extract information from the sentences to transform them into nodes and edges in the story world graph. The system would then use the data in the story world graph to look for events and event chains, and use natural language generation techniques to generate a summary. The resulting story summary would not be more than half the length of the original story.